Hydrogeochemical characteristics and environmental significance of travertine landscape in Muji area - Rui AN; Miao SUN; Yiwei ZHANG; Bin LI; Wenpeng LI; Kun LIU (Shuiwen dizhi gongcheng dizhi)
Travertine is a type of karst deposit widely distributed worldwide. Groundwater in karst areas is the main component of global water resources, providing a large number of ecological services and urban water supply. It is urgent to strengthen the investigation of its environmental status and the assessment of water resources security. This study analyzed the hydrochemical characteristics of groundwater and the distribution of 21 trace heavy metals in a typical travertine landscape in Muji, Xinjiang. The results show that the groundwater solutes in the travertine landscape in this region were dominated by calcium and magnesium ions, with an overall HCO3—Ca type. Iron, manganese, and strontium were the main metals exceeding the standard. Weathering of rocks and mineral dissolution were the main processes controlling the groundwater chemical properties in this region, consistent with the analysis of the chemical composition of coated particles. 57% of the samples exhibited significant contamination with heavy metals. Among these, manganese, strontium, and cobalt were identified as potential non-carcinogenic health risks to humans, and arsenic was found to pose carcinogenic risks. This study emphasizes that attention should be paid to the changes in hydrochemical characteristics and risk-increasing effects of rock weathering process on groundwater in travertine landscape. Based on the need for the protection of travertine landscape and human drinking water safety, our results are of great significance for understanding the characteristics of hydrochemical environment shaped by travertine landscape, effective protection, and rational use of groundwater in karst areas.